A Roman Amulet in the National Museum of Archaeology - Correia, Virgílio Hipólito (Conimbriga, 2020)
A Roman amulet of the “magic gemstone” kind is published. It belonged to the collection of Vergílio Correia, now kept in the National Museum of Archaeology, and probably comes from Conimbriga.